Places of Sanctuary in the Artistic Work of Liz Johnson Artur - Dzifa Peters (The February Journal)
This essay deals with the concept of sanctuary in relation to Afrodiasporic and postmigrant formations of identity. It discusses coexisting and alternating cultural identities through the work of Russian-Ghanaian artist and photographer Liz Johnson Artur, who has been accumulating her Black Balloon Archive of Black culture and diasporic identities for the past 30 years, travelling through different countries, lifestyles, and classes. The idea of the sanctuary as a place of refuge, safety, and hospitality has informed the discourse around diasporic migration in a postcolonial world for many decades. Comparatively analyzing the politics of representation and discourses on agency through Johnson Artur’s cross-cultural and intimate photographic practice, this essay explores her articulation of conditional shelters, demarcations of diasporic identities, and ultimately the archive itself as a place of sanctuary.